Computational Analysis: Fluid Structure Interaction Model Of The Mitral Valve Leaflet - Mohd Azrul Hisham, Mohd Adib (2010)

(untitled)
In the mitral valve, regional variations in structure and material properties combine to affect the biomechanics of the entire valve. Previous study, we know that mitral valve leaflet tissue is highly extensible. So, the objective of this study was to investigate the correlation between the rigidity of mitral valves leaflet and backflow problem based on critical parameter of blood. Two stages of mitral valves analysis systolic and diastolic stages and also with and without ventricle were investigated. Two dimensional models of the mitral valve leaflet were created in ADINA-FSI for computational fluid dynamic analysis. The results show linear correlation between rigidity of the mitral valves leaflet and volume of backflow. In conclusions, these computational techniques are very useful in the study of both degenerative valve disease and failure of prostheses. Findings are the prediction of the behavior of the mitral valves leaflet and blood flow which can assist the medical practitioners in their decision on the patient treatments.